Cancer Systems Biology: Methods and Protocols - Stechow, Louise von (Methods in Molecular Biology, 2018)
Detection of Combinatorial Mutational Patterns in Human Cancer Genomes by Exclusivity Analysis -- Discovering Altered Regulation and Signaling Through Network-based Integration of Transcriptomic, Epigenomic, and Proteomic Tumor Data -- Analyzing DNA Methylation Patterns during Tumor Evolution -- MicroRNA Networks in Breast Cancer Cells -- Identifying Genetic Dependencies in Cancer by Analyzing siRNA Screens in Tumor Cell Line Panels -- Phosphoproteomics-based Profiling of Kinase Activities in Cancer Cells -- Perseus: A Bioinformatics Platform for Integrative Analysis of Proteomics Data in Cancer Research -- Quantitative Analysis of Tyrosine Kinase Signaling Across Differentially Embedded Human Glioblastoma Tumors -- Prediction of Clinical Endpoints in Breast Cancer using NMR Metabolic Profiles -- Stochastic and Deterministic Models for the Metastatic Emission Process: Formalisms and Crosslinks -- Mechanically Coupled Reaction-Diffusion Model to Predict Glioma Growth: Methodological Details -- Profiling Tumor Infiltrating Immune Cells with CIBERSORT -- Systems Biology Approaches in Cancer Pathology -- Bioinformatics Approaches to Predict Drug Responses from Genomic Sequencing -- A Robust Optimization Approach to Cancer Treatment under Toxicity Uncertainty -- Modeling of Interactions between Cancer Stem Cells and their Microenvironment: Predicting Clinical Response -- Methods for High-throughput Drug Combination Screening and Synergy Scoring. .